Implementasi Program Padat Karya Tunai Dari Dana Desa dalam Mengatasi Kemiskinan Masyarakat Desa Karang Gading - Hajar Risa; Badaruddin Badaruddin; Munir Tanjung (PERSPEKTIF, 2021)
The purpose of this study was to analyze the implementation, constraints and impact of the implementation of the cash for work program in Karang Gading Village on the poverty of the people of Karang Gading Village, Labuhan Deli District, Deli Serdang Regency. This research uses a qualitative descriptive method, to make descriptions, pictures, or paintings systematically and accurately about the facts, characteristics and relationships between the phenomena being investigated. The results showed that the implementation of the cash for work program from the Karang Gading Village Fund on the concrete rebate activity for sirtu hoarding in Dusun VI for the 2020 fiscal year the results were not optimal, this can be seen from four aspects in accordance with Edward III's theory of communication that is not yet optimal, Resources are inadequate, the Bureaucratic Structure is not completely well organized, and only the Disposition / Attitude is sufficient, the obstacles faced are inadequate human resources, and minor conflicts in the form of protests from villagers who are not empowered as workers or recipients. Village Cash Workforce Wages and rumors circulating that the Village Head and TPK only empower families and relatives as workers / recipients of Village Cash Workforce wages.